2008
DOI: 10.5458/jag.55.231
|View full text |Cite
|
Sign up to set email alerts
|

.BETA.-Glucans in the Water-insoluble Residue of Hericium erinaceum

Abstract: Fruiting bodies of Basidiomycetes mushrooms have been attracted increasing attention of pharmaceutical and functional food industry because of their health promotion and disease alleviation effects on human health. 1) On account of bioactive and medicinal activities, immune stimulation, anti inflammatory antimicrobial, antitumoral, hepatoprotective, cholesterol lowering properties are representative as well as antifibrotic, antidiabetic and hypoglycemic activities.2 6) The origin of these effects are best know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, during microwave heating, disruption of weak hydrogen bonds occurs due to dipolar rotation of molecules. It accelerates the rupture of cells leading to a sudden rise in temperature and buildup of internal pressure inside the cell walls of plant tissue (Ahmad and Langrish, 2012;Ookushi et al, 2006Ookushi et al, , 2008aOokushi et al, , 2008bTsubaki et al, 2009Tsubaki et al, , 2010Xiao et al, 2009). Sun et al (2007) have employed a MAE process for extracting hesperidin from Pericarpium citri reticulate (dried pericarp of the ripe fruit of C. reticulate) using 70% aqueous methanol as a solvent and the results showed that MAE is an efficient, fast, and energysaving method.…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…Also, during microwave heating, disruption of weak hydrogen bonds occurs due to dipolar rotation of molecules. It accelerates the rupture of cells leading to a sudden rise in temperature and buildup of internal pressure inside the cell walls of plant tissue (Ahmad and Langrish, 2012;Ookushi et al, 2006Ookushi et al, , 2008aOokushi et al, , 2008bTsubaki et al, 2009Tsubaki et al, , 2010Xiao et al, 2009). Sun et al (2007) have employed a MAE process for extracting hesperidin from Pericarpium citri reticulate (dried pericarp of the ripe fruit of C. reticulate) using 70% aqueous methanol as a solvent and the results showed that MAE is an efficient, fast, and energysaving method.…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…Due to different preparation methods, the structure, molecular weight, and other properties of the resulting Hericium erinaceus polysaccharides can also vary greatly. In terms of solubility, are they mainly water-soluble and alkali-soluble, in terms of molecular weight, their order of magnitude is in the range of 105-106, and in terms of structure, they mainly consist of β-(1→3) and β-(1→6)-glycosidic bonds, in which the molar ratio of the two types of glycosidic bonds differs greatly [22][23][24][25][26]. The significant structural differences in the β-glucan of Hericium erinaceus can be used as an ideal representative of the β-glucan of edible bacteria, providing a good model for studying the effect of different preparation methods and different structures on the regulation of the species structure of human fecal intestinal flora.…”
Section: Introductionmentioning
confidence: 99%